Niemann-pick disease type A-a case report - Tangde, Ashwini; Pore, Shubhajyoti; Kulkarni, Anjali; Joshi, Anil; Bindu, Rajan (International Journal of Research in Medical Sciences, 2017)
Niemann-Pick Disease is an autosomal recessive disorder of infancy, characterized by failure to thrive, hepatosplenomegaly and neurodegenerative changes. It is caused by inherited deficiency of an enzyme, acid sphingomyelinase. It leads to deposition of sphingomyelin and cholesterol within the lysosome of reticuloendothelial cells of various organs. Niemann-Pick Disease is classified into four types such as A, B, C and D. We present a case of niemann-pick disease type A. This case report encompasses an 18-month-old male child brought with complaints of progressive abdominal distension, developmental delay, intermittent fever and excessive cry. On examination patient had developmental delay and significant abdominal distension with moderate hepatosplenomegaly. Bone marrow examination showed characteristic lipid laden foamy histiocytes termed as niemann pick cells and sea blue histiocytes. Later on, liver biopsy and splenic aspiration cytology was performed, which also showed same type of foamy cells. Type A is very rare and a severe infantile form with neurologic degeneration resulting in death usually by 3 years of age. No treatment available for type A so far. It’s a rare disease in India. Genetic counseling.